PERANCANGAN SISTEM INFORMASI AKUNTANSI PERSEDIAAN OBAT MENGGUNAKAN MICROSOFT VISUAL STUDIO 2010 DI APOTEK ASSIDIQIYAH GARUT - Rahmawati Salim, Elisa; Nurrohman, Taufik; Karyadi, Karyadi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This research aims to design an accounting information system of medicine inventory using Microsoft Visual Studio 2010 in Assidiqiyah Garut pharmacy. Assidiqiyah pharmacy is a place of professional dedication for the pharmacist who has taken the pharmacist’s oath or promise. The activities carried out are compounding and delivering medicine. The research method that is used is a qualitative method, with data collection techniques are observation, interview, documentation, literature study, and website. The development method that is used is the waterfall method. The author uses a complete system, namely Flowmap, context diagram, Data Flow Diagram Level 0, and Entity Relationship Diagram, which is input from drug inventory data, the process consists of transactions for drug submissions, drug receipts, drug dispensing, and general journals, while the output is a report transaction and general journal reports. The problem that was found was recording data was still used a manual recording system only using the ledger, which that susceptible to errors in reporting data. The author hopes that this research on the design of the drug supply information system can help the process of recording drug supplies at the Assidiqiyah Pharmacy. The suggestions that are given are 1) there is training for admins who will use the system. 2) This system was continuously developed to meet institutional needs. 3) This system should be maintained to prevent a system failure.